Organelle contact zones as sites for lipid transfer. (29th October 2018) - Tamura, Yasushi; Kawano, Shin; Endo, Toshiya
Abstract: Since the 1950s, electron microscopic observations have suggested the existence of special regions where the distinct organelle membranes are closely apposed to each other, yet their molecular basis and functions have not been examined for a long time. Recent studies using yeast as a model organism identified multiple organelle-membrane tethering sites/factors, such as ERMES (ER –m itochondriae ncounters tructure), NVJ (N uclear–v acuolej unction), vCLAMP (V ac uol ea ndm itochondriap atch) and MICOS (Mi tochondrialco ntacts ite). Among them, ERMES is the best-characterized contact-site protein complex, which was found to function as not only an organelle-tethering factor but also a phospholipid transfer protein complex. In this review, we will discuss recent advances in the characterization of ERMES and other organelle contact zones, vCLAMP, NVJ and MICOS in yeast.